A software platform controlling an MRI guided focused ultrasound system - Damianou, Christakis A.; Yiallouras, Christos; Alexis, Alexandrou; Marinos, Ioakim; Hadji Savvas, Venediktos; Milonas, Nicos (My University, 2012)
A software platform written in MATLAB has been developed in order to control an MRI guided Focused ultrasound system. The software serves 7 main tasks: a) MRI imaging, b) transducer movement (the user may move the robot manually or automatically by specifying the pattern, the step and the number of steps), c) messaging (starting time, treatment time left etc), d) Camera control, e) Patient data (age, weight, etc), f) Controlling the parameters and activation of a signal generator and g) Temperature measurement. The motors are activated using a 24 V DC supply which is incorporate in an enclosure that includes the drivers of the motors. The motors are interfaced using a USB card (National instruments NI-6251). Feedback is provided using a timer card. The software controls a positioning device which can be used to treat patients with brain, liver, kidney, thyroid, pancreas and prostate cancer. © 2012 IEEE.
Keywords: HIFU; MRI; software